Stakeholder outcome prioritization in the Biologic Abatement and Capturing Kids' Outcomes and Flare Frequency in Juvenile Spondyloarthritis (BACK‐OFF JSpA) trial - Emily Neu; Cora Sears; Timothy Brandon; Melanie Kohlheim; Jenny Leal; Kweli Archie; English Holland; Miles Holland; Aamena Hameed; Asad Khan; Lynn Murphy; Sean Murphy; et al. (Health Expectations, 2023)
Abstract Background The Biologic Abatement and Capturing Kids’ Outcomes and Flare Frequency in Juvenile Spondyloarthritis (BACK‐OFF JSpA) study is a randomized, pragmatic trial investigating different tumour necrosis factor inhibitor de‐escalation strategies for children with sustained inactive disease. In this project, we elicited concept rankings that aided in the selection of the patient‐reported outcome (PRO) measures that should be examined as part of the BACK‐OFF JSpA trial. Methods We conducted a discrete choice experiment to evaluate individuals' preferences regarding PROs. Stakeholders assessed a discrete list of 21 outcome concepts, each of which had a Patient‐Reported Outcome Measurement Information System (PROMIS) measure associated with it. PROMIS measures are self‐ or proxy‐reported instruments that are universally applicable to the general population and all chronic conditions. Stakeholders were required to make choices instead of expressing the strength of a preference. Results Fourteen caregivers, 12 patients (9–22 years old), 16 rheumatologists and three executives from health insurance companies completed the exercise, which took approximately 10 min. The discrete choice experiment resulted in an estimate of the relative importance of each outcome and rank. All stakeholder groups agreed that the primary PRO should be ‘Pain Interference’, a measure that evaluates the effect of pain on a child's everyday activities, including its impact on social, emotional, mental and physical functioning. Patients and caregivers were mostly aligned in their top priorities, with patients valuing physical health (50% of the top 10) whereas caregivers were more interested in mental health (60% of the top 10). Rheumatologists and health insurance executives were most interested in physical health outcomes, which were ranked 80% and 60% of their top 10 PROs, respectively. Overall, the patients had the most diverse set of prioritized outcomes, including at least one of each category in their top 10 rank order of importance. Patients were also the only stakeholders to prioritize ‘social’ health. Conclusions Patients and caregivers were mostly aligned in their outcome priority rankings. The rank‐order list directly informed the creation of a profile of PRO measures for our upcoming trial. Patient or Public Contribution Stakeholder partners helped with acquisition of data and lead parent partners helped interpret data.